A Promising Ultra-Small Unilamellar Carrier System for Enhanced Skin Delivery of α-Mangostin as an Anti-Age-Spot Serum - Ully Chairunisa; Rustini; Christofori Maria Ratna Rini Nastiti; Florentinus Dika Octa Riswanto; Heather A. E. Benson; Henny Lucida (MDPI AG, 2022)
If it can be effectively delivered to its site of action, α-mangostin has potential in development of novel cosmeceuticals due to its melanogenesis-blocking activity. The aim of this study was to develop an ultra-small unilamellar carrier system for α-mangostin and to evaluate its effect as an anti-age-spot serum on humans in vivo. The ultra-small unilamellar carrier bases were optimized using a 25 factorial design, with five factors (virgin coconut oil, soy lecithin, Tween 80, and stirring duration and speed) and two levels (low and high); response of droplet size was analyzed using Design Expert 12®. The anti-spot examination was conducted via capturing digital images of the human skin after topical application of an α-mangostin-loaded ultra-small unilamellar carrier at night for two consecutive weeks. The results thereof were analyzed using Motic Live Imaging 3.0 and a standard red, green, and blue score. The optimized serum formula was confirmed with a composition of 2.3% virgin coconut oil, 1% lecithin, and 28.3% Tween 80 (polysorbate 80) at a stirring speed of 1500 revolutions per minute for 15 min. Incorporation of 3% α-mangostin to the optimized base formula produced an ultra-small unilamellar carrier globule size of 16.5 nm, with zeta potential of −25.8 mV and a polydispersion index of 0.445. Physical characterization of an α-mangostin-loaded ultra-small unilamellar carrier comprised 90.94% transmittance, a pH value of 6.5, a viscosity of 38 cP, specific gravity of 1.042 g/mL and 72.46% entrapment efficiency. A transmission electron microscope confirmed spherical nanosized droplets in the system. Topical application of an α-mangostin-loaded ultra-small unilamellar carrier at night for 2 consecutive weeks demonstrated anti-age-spot activity shown through a significant reduction in intensity and area of spots in human volunteers (p < 0.05).